2010
DOI: 10.1258/ijsa.2009.009464
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of proximal renal tubular dysfunction in patients on tenofovir disoproxil fumarate

Abstract: The concern about the specificity of nucleic acid amplification tests (NAATs) in low prevalence GC populations is associated with its false positivity (cross-reactions with different Neisseria species) impacting on positive predictive value. Not all NAATs are the same and this type of false positivity has not been observed with AC2 to date. 2,3 In Cheshire and Merseyside, UK, we have since 2004 incorporated dual testing for chlamydia (CT) and GC into our chlamydia screening programmes using the Gen-Probe Apt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…First, four patients (2.9%) in our study had serum Cr levels that increased more than 1.5 mg/dL during HAART. Other study that treated 10,000 HIV-infected patients with TDF and monitored the increase in serum Cr found that 2.2% of cases showed baseline serum Cr more than 0.5 mg/dL and 0.6% increased more than 2.0 mg/dL [ 8 ], which was similar to our results. Second, the four patients whose serum Cr increased more than 1.5 mg/dL were administered both TDF and a PI/r drug.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…First, four patients (2.9%) in our study had serum Cr levels that increased more than 1.5 mg/dL during HAART. Other study that treated 10,000 HIV-infected patients with TDF and monitored the increase in serum Cr found that 2.2% of cases showed baseline serum Cr more than 0.5 mg/dL and 0.6% increased more than 2.0 mg/dL [ 8 ], which was similar to our results. Second, the four patients whose serum Cr increased more than 1.5 mg/dL were administered both TDF and a PI/r drug.…”
Section: Discussionsupporting
confidence: 91%
“…Nephrotoxicity can appear either during long or short-term use of TDF. TDF-induced nephrotoxicity is reported in about 15% of patients treated with TDF for 2-9 years [ 8 ]. Previous studies have reported several risk factors for TDF-induced nephrotoxicity, including high basal serum creatinine (Cr) level, concomitant use of nephrotoxic drugs, low body weight, old age, and low CD4+ T cell count [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous case reports and case series have described severe cases of renal tubular toxicity associated with TDF exposure [3-5]. It is estimated that renal tubular dysfunction develops in nearly 15% of patients treated with tenofovir for 2–9 years [6]. Tubular dysfunction may precede the decline of renal function [7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, long-term use of TDF is associated with risk of renal tubular dysfunction [80][81][82]. ART is not currently an over-the-counter medicine.…”
Section: Preexposure Prophylaxismentioning
confidence: 99%